Implementasi Kebijakan Alokasi Dana Desa di Desa Sumberkolak Kecamatan Panarukan Kabupaten Situbondo (Jurnal Strategi dan Bisnis, 2014)
The purpose of this study is to provide an overview on the implementation of the village fund allocation Sumberkolak Village District Panarukan Situbondo. The informants are the implementation team to the allocation of village funds, namely: sumbekolak village head, village fund allocation implementation team and BPD. Based on data analysis, the results showed that the village fund allocation policy implementation in the Village District Panarukan Sumberkolak Situbondo less successful because the head of the village as the administrator does not perform properly function. In addition, based on the process of formation of the implementation team, work plan development process, the allocation of funds, time, human resources, territory, and reporting are not implemented properly. Several factors, such as: communication, resource capabilities, attitudes and implementing bureaucratic structures are not performing well. Keywords: implementation of public policy, the administrator